The Role Of Religiosity And The Factors That Influence Purchase Intention On Halal Cosmetics In Batam City - Saputra, Suyono; Yulfiswandi; Yuliyanti (ADPEBI International Journal of Business and Social Science, 2023)
This study aims to determine the effect of subjective norms, knowledge, and religion on attitudes and purchase intentions of halal cosmetics in Batam. The method used in this study is a quantitative method. The object of this research is consumers who have used halal cosmetics in Batam City. This research was conducted by survey method by distributing questionnaires in the form of Google Forms to 350 respondents in Batam City. After the questionnaires were distributed and collected by the authors, there were 305 questionnaires that could be used to process data using the SmartPLS program. The results of this study indicate a significant relationship between subjective norms, knowledge, and religious variables on consumer attitudes and a significant relationship between religious variables and consumer attitudes toward purchase intentions. Then there is an insignificant relationship between subjective norms and purchase intention. The results of this study are expected to be a reference for students in the marketing field who want to examine the factors that influence the purchase intention of halal cosmetics.